Conservation value of dispersed tree cover threatened by pasture management - Harvey, Celia A. (2011)
Trees dispersed in pastures are a prominent feature of many Central American landscapes, particularly in cattle producing regions where farmers retain trees to serve as shade, fodder, timber and firewood. The presence of dispersed trees in pastures is often considered as important for the conservation of biodiver sity by providing habitat and enhancing landscape connectivity. However, despite their critical productive and environmental roles, little is known about tree distribution within pastures or how farmers’ man agement decisions influence the trees themselves and their impact on farm productivity and biodiversity conservation. Here, we present a synthesis of (a) the abundance, composition, and size of dispersed trees in four important cattle producing regions of Costa Rica (Canas and Río Frío) and Nicaragua (Rivas and ˇ Matiguás), based on inventory of 18,669 trees on 1492 ha of pasture, (b) the local knowledge, manage ment and use of trees by cattle farmers, and (c) opportunities for ensuring sustainable management of dispersed trees in pasture-dominated landscapes. Dispersed trees were common in all four landscapes, with mean frequency ranging from 8.0 trees ha−1 in Canas to 33.4 trees ha ˇ −1 in Matiguás. A total of 255 tree species were found in pastures across the four landscapes. The total number of tree species per land scape varied from 72 in Rivas to 101 in Canas and Rio Frio, with mean species richness per farm ranging ˇ from 22.9 in Rio Frio to 45.9 in Matiguás.